Анатомічна будова дворічних пагонів тополь секцій Aegirus Doby і Tacamahacae L. Spach - Gryshko, V.N.; Danilchuk, A.V. (M.M. Gryshko National Botanical Garden of the NAS of Ukraine, 2010)
The anatomic structure of two-year shoots of the real poplars in the conditions of Right-Bank Steppe Pridneprov’ya is studied. At the poplars of Tacamahacae L. Spach section (Populus candicans Ait., P. suaveolens Fisch. and P. simonii Carr.) is formed less primary bark, while at the species of Aegirus Doby section (P. deltoides Marsh. and P. italica (Du Roi) Moench) is the less second bark. For the last is characteristic the laying of hard bast both separate metameres and continuous layers, while for the representatives of Tacamahacae section – separate metameres. Wood of all investigated species is dissipated type. Core at P. deltoides, P. pyramidalis, P. candicans and P. suaveolens shoots has a starry form, and at P. simonii – more rounded.